Content Analysis of 2012-2019 FDA Warning Letters and Notices of Violations using the Economic, Clinical, and Humanistic Outcomes (ECHO) Model - Namosha Mohite; Vienica Funtanilla; Jagannath Muzumdar; Taehwan Park (University of Minnesota Libraries Publishing, 2021)
Objective: The study purpose was to critically review FDA-issued warning letters (WLs) and notice of violation (NOV) letters against drug companies' from 2012-2019 for economic, clinical, and humanistic (ECHO) claims made in pharmaceutical promotional materials. Specific objectives were to assess the, (1) number of WLs and NOV issued; (2) frequency of WLs and NOV by therapeutic areas; (3) type of communication media cited in WLs or NOV; (4) intended audience for the claims in promotional materials for which the WLs and NOV were issued; and (5) number of WLs and NOV for ECHO claims. Methods: The quantitative content analysis approach was employed to review WLs and NOVs, obtained from the FDA website, from January 2012-December 2019. A data abstraction form was created based on the published literature on this topic and assessment of the content of WLs and NOVs for 2010. This form was pilot tested on letters issued in 2011. The researchers discussed any unclear question or information presented in the letters. The letters were reviewed three researchers. If there was disagreement between the reviewers, either a fourth reviewer arbitrated on the disagreement or the letter(s) were discussed by the researchers to determine a final classification. ICD-10 codes were used for therapeutic categories in the data collected form. Descriptive statistics, Kappa statistics for interrater reliability, and Cochrane-Armitage test were performed using IBM SPSS Statistics version 24.0 Results: A total of 102 letters were analyzed. Of these, 19 (19%) were WLs and 83 (81%) were NOVs. Majority of these letters were issued to manufacturers of therapeutic agents for diseases of the nervous system (n=15; 14.7%) and neoplasms (n=15; 14.7%). The most commonly cited media for violation was online website (n=29; 27.1%). Out of the 153 violations in 102 letters, 92 (60.1%) were clinical; 13 (8.5%) humanistic; 2 (1.3%) were economic; and 46 (30%) were categorized as 'Others'. Conclusion: The study found misleading claims of the clinical effectiveness and risk information included in the promotional materials targeted to consumers as well as healthcare providers. Promoting reliable, evidence-based information is important for the health of the public as inadequate information could lead to irrational decision making both on consumer as well as on prescriber side.